Socio-Educational Environment as a Factor Differentiating the Age of Menarche in the Bydgoszcz Region - Nowicki, Grzegorz (Anthropological Review, 1996)
This paper presents the results of research on the age of menarche of the Polish girls in the Bydgoszcz region.